Łódź Statistics and Demography Facing New Challenges: Institute of Statistics and Demography - Bolonek-Lasoń, Katarzyna; Grzelak, Maria M.; Jędrzejczak, Alina; Rossa, Agnieszka; Wiktorowicz, Justyna (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and current development of the Institute of Statistics and Demography at the Faculty of Economics and Sociology, University of Łódź. The authors discuss its academic and teaching traditions, focusing particularly on the last decade.